Tracheostomies for respiratory failure are associated with a high inpatient mortality: a potential trigger to reconsider goals of care - Mackenzie Cook; Cameron Colbert; Aaron D Streblow; Scott P Sherry; Konrad Dobbertin (Trauma Surgery & Acute Care Open)
Introduction Acute care surgeons are frequently consulted for tracheostomy placement in the intensive care unit (ICU). Tracheostomy may facilitate ventilator weaning and improve physical comfort. Short-term outcomes after tracheostomy are not well studied. We hypothesize that a high proportion of ICU patients who underwent tracheostomy died prior to discharge. These data will help guide clinical decision-making at a key pivot point in care.Methods We identified 177 mixed ICU patients who received a tracheostomy for respiratory failure between January 2013 and December 2018. We excluded patients with trauma. Patient information was collected and comparisons made with univariable and multivariable statistics.Results Of the 177 patients who underwent a tracheostomy for respiratory failure, 45% were women, median age was 63 (51–71) years. Of this group 18% died prior to discharge, 63% were discharged to a care facility and only 16% discharged home. Compared with survivors, patients with tracheostomies who died during their admission were older, age 69 (64–76) versus 61 (49–71) years (p<0.01) on univariable analysis. In this model, no single comorbid condition or length of stay (LOS) variable was predictive of death before discharge. A multivariable model controlling for covariation similarly identified age, as well as a longer ICU LOS of 34 (20–49) versus 23 (16–31) days (p=0.003) as factors associated with increased likelihood of death before discharge.Conclusions Tracheostomy placement in a mixed ICU population is associated with a nearly 20% inpatient mortality and the vast majority of surviving patients were discharged to a care facility. This suggests that the need for tracheostomy could be considered a trigger for re-evaluation of patient goals. The high risk of death due to underlying illness and high intensity care after their hospitalization emphasize the need for clear advanced care planning discussions around the time of tracheostomy placement.Level of Evidence Level IV, Retrospective cohort study.